KEBIJAKAN POLITIK AFIRMATIF DAN PROBLEMATIKA REPRESENTASI PEREMPUAN DI PARLEMEN LOKAL PADA DPRD KABUPATEN WONOSOBO - Winata, Tirta Pandu; Putri, Rizky Amalia; Tirta Pandu Winata; Rizky Amalia Putri (Universitas Islam Negeri Raden Intan Lampung, 2024)
The implementation of the decentralization system in Indonesia has intensive implications of the massive public attention to gender equality discourse. In the political aspect, the realization of the egalitarian principle between men and women has been pursued through affirmative political policies that seek to fulfill the minimum participation of women in parliament as much as 30%. But this precious hope is not easy to realize. The case study conducted in Wonosobo Regency illustrates the complex reality of gender equality, where since the 1999 elections, in the first year of the implementation of the decentralization policy until the 2019 elections, the minimum quota of 30% women's participation in local parliaments has never been fulfilled. In fact, in the 2019 elections, only one woman was elected as a member of the Regional People's Representative Council (DPRD). This study aims to analyze the factors that make it difficult to realize the principle of at least 30% women's representation in the DPRD of Wonosobo Regency, which has even been encouraged by affirmative political policies. The method used in this research is a qualitative method with a case study approach. The results of this study indicate several factors that influence the difficulty for women to occupy seats in regional parliaments, including institutional factors and political funding, religious doctrination, gender bias that is rooted in society, and leadership in political parties. The conclusions in this study illustrate the difficulty of fulfilling the principle of at least 30% women's representation in the DPRD of Wonosobo Regency caused by various factors, and not only because of the patriarchal culture that exists in society.